Pomniki przyrody gminy Gubin i Brody = The natural monuments in the municipalities of Brody and Gubin - Markulak, Damian (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the natural monuments located in the municipalities of Brody and Gubin. An attempt was made to catalog the monuments of nature, which may suffer as a result of the planned exploitation of lignite deposits located within these municipalities.
Keywords: pomniki przyrody; oddziaływanie na środowisko; natural monuments; environmental impact